W.P. Visser, Van MWU tot Solidariteit: Geskiedenis van die Mynwerkersunie 1902-2002 Solidariteit, Centurion, 2008: An organisational and political history (Historia, 2021)
Labour history, very much including the history of labour organisations, loomed large as a project amongst the revisionist historians of the 1970s and 1980s ; they explored themes such as the interrelationship of class and politics in work which was highly politicised responding to the growing black labour resistance to the state. The study of white unionists and white labour, especially in the first militant quarter of the twentieth century, was a major part of this project. However, subjects that slid off the political screen were neglected. Nobody could deny the economic importance of the gold mining industry, but white gold miners? Once past the heroic - if at times misguided - phase of semi-insurrections leading up to the Rand Revolt of 1922, these overtly racist beneficiaries of the colour bar were best ignored, simply part of the problem. Thus we can feel very indebted to Wessel Visser for his painstaking attempt to fill this major gap. Without painting a more attractive picture of white gold miners than is justified, he has significantly added to South African labour history with this lengthy monograph, the first published book-length study of the Mine-Workers' Union (MWU). The organisation of the work into chronically logical chapters gives convincing shape to this study which covers several generations of economic history.